Factors Influencing Users’ Intentions to Use Mobile Applications in Hospitals - Haryono; Agung Wicaksono Kusumawardhana (Universitas Teknologi Yogyakarta, 2021)
e-Health app is an application system that potentially could increase the efficiency and effectiveness of a hospital's performance. The developers need to know e-health app impacts, such as usefulness, easy use, and the overall impact to the users. This research identifies and evaluates factors influencing users' intentions and prospective users using an easy-to-Health (e-Health) app named RSA UGM Online application. Prospective users are included in this research as samples to help the application developer understand their potential market regarding product effectiveness. This research aims to identify and analyze factors influencing the use of the electronic-Health Technology Acceptance Model (e-HTAM) to increase a hospital's performance efficiency and effectiveness. A hypothetical model testing was conducted through empirical data collection, 403 experienced and inexperienced respondents on using RSA UGM Online application, using online and offline surveys. The structural Equation Model was used to assess the significance of the path coefficient. The research results show that the Perceived Usefulness, Subjective Norm, and Technology Design of the RSA UGM Online application can predict the users' intentions and prospective users. It recommends the application developer developing an e-health app based on the three factors that are successfully tested affecting their users’ intentions.